Draft genome sequences of helicobacter pylori isolates from Malaysia, cultured from patients with functional dyspepsia and gastric cancer - Gunaletchumy, S.P.; Teh, X.; Khosravi, Y.; Ramli, N.S.K.; Chua, G.E.; Kavitha, T.; Mason, J.N.; Lee, H.T.; Alias, H.; Zaidan, N.Z.; Buang M. Yassin, N.; Tay, L.C.; et al. (2012)
Helicobacter pylori is the main bacterial causative agent of gastroduodenal disorders and a risk factor for gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. The draft genomes of 10 closely related H. pylori isolates from the multiracial Malaysian population will provide an insight into the genetic diversity of isolates in Southeast Asia. These isolates were cultured from gastric biopsy samples from patients with functional dyspepsia and gastric cancer. The availability of this genomic information will provide an opportunity for examining the evolution and population structure of H. pylori isolates from Southeast Asia, where the East meets the West